Plan de negocios para la importación, transformación y comercialización, en la ciudad de Quito, de una tela de microfibra y de secado rápido que ayuda a la absorción del sudor - Correa Paredes, Doménica Belén (2017)
The following business plan is based on importing, transforming and selling a microfiber fabric, which can absorb sweat of the skin. The product goes to people with hyperhidrosis, athletes and/or individuals who perform urban sports like going to their job, university, etc. and wish to take care of their appearance and/or their health. In order to see the viability of the project, studies were carried out, one qualitative and the other quantitative; both gave ideas of possible customer preferences to adapt the products so that its sales turn out successful. Additionally, they contributed with marketing and sales strategies to position the brand in the minds of consumers and avoid the purchase of the product of the competition, either inside the country or outside of it. In conclusion, 92% of the people in the studies the accepted the idea had and the financial indicators show that the business is viable. The initial investment is of 74.322,74 USD placing 65% of own capital and 35% financed by the Bank of Pichincha.